Integrasi Pembelajaran Berbasis Proyek di SMK untuk Pengabdian Masyarakat melalui Implementasi Teknologi Energi Terbarukan - Sumardi, Sumardi; Hartono, Akhmad Muji; Viendasari, Mila (Universitas Perjuangan Tasikmalaya, 2026)
The Sustainable Development Goals face challenges such as disparities in energy access and limited skilled human resources. This research aims to analyze the effectiveness of a cross-sector synergy model centered on vocational high schools (SHSs), which act as agents of sustainable community empowerment. This study utilizes a qualitative case study examining a projectbased learning program in which students majoring in Renewable Energy at SMKN 1 Lingsar were directly involved in the design and installation of clean technology in schools and communities. The results indicate that this collaborative approach successfully improved students' technical and nontechnical competencies, provided energy access that fostered local economic independence, and established an efficient partnership model. It is concluded that integrating vocational education into a multi-stakeholder synergy is an effective strategy for transforming vocational high schools into catalysts for sustainable development.